Історико-правові аспекти становлення поглядів на мету кримінально-виконавчого законодавства України - Осауленко, Андрій Олександрович; Осауленко, Андрей Александрович; Osaulenko, Andrej (Одеса : Юрид. л-ра, 2014)
In the article the historical and legal aspects of the formation of views on the purpose of penal criminal legislation of Ukraine are explored, relevant scientific approaches and their reflection in the legal acts in the last 60 years are analyzed. In the context of investigated problems special attention was paid to the legal acts and legal doctrine of the USSR. The author emphasizes the convict emendation and resocialization are considered as the main law guidelines for implementation of criminal penalties and represent the complex psychological, educational, social and legal categories. As one of the components of the goal of penal criminal legislation is prevention of new crimes by convicts and others.
Осауленко А. О. Історико-правові аспекти становлення поглядів на мету кримінально-виконавчого законодавства України / А. О. Осауленко // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 96-102.
Keywords: мета кримінально-виконавчого законодавства; покарання; виправлення; ресоціалізація; засуджений; цель уголовно-исполнительного законодательства; наказание; исправление; ресоциализация; осужденный; purpose of penal criminal legislation; judgment; emendation; resocialization; convict